A CALPHAD approach to modelling of slag viscosities. (June 2019) - Hack, K.; Wu, G.; Yazhenskikh, E.; Jantzen, T.; Müller, M.
Abstract: A structure-based model recently developed for the fully liquid system SiO2 –Al2 O3 –CaO–MgO–Na2 O–K2 O–FeO–Fe2 O3 in the Newtonian range is presented in this paper and the methodology to modelling of the viscosity is outlined. In the model, the structural treatment of the various oxides in multicomponent oxide systems is discussed on the basis of the underlying non-ideal associate species model that was used to describe the Gibbs energy of the liquid. Both the temperature- and composition-induced structural changes of oxide melts is then described with a set of monomer associate species in combination with some specific larger structural units induced by the self- and inter-polymerisations of the associate species. On the other hand, the overall performance of the viscosity model will be demonstrated and discussed. One of the challenges of the viscosity behaviour in SiO2 -based binary systems, the so called lubricant effect, is well described. The local viscosity maximum around the fayalite composition in the system FeO–SiO2 is also sufficiently described. The viscosity behaviour when substituting one network modifier for another at constant SiO2 contents is properly described. Moreover, the Al2 O3 -induced viscosity maximum is described, in which the position and magnitude of the viscosity maximum as a function of temperature and composition (charge compensation effect) are properly predicted. In addition to a good performance in describing the various challenging viscosity behaviours, the model parameters bear a clear physico-chemical meaning, which ensures a reliable prediction over the whole range of compositions and a broad range of temperatures and oxygen partial pressures (for iron oxide-containing systems). Finally, in combination with phase relations the model is employed to determine the blending proportions for coal slags according to a target viscosity value, as an application case. Highlights: A structure based viscosity model is developed for multicomponent oxide systems. The model covers the whole range of compositions and a broad range of temperatures. Good performance is achieved using only model parameters for low order systems. Composition induced complex viscosity behaviours are well described. Application of the model in determining the blending proportions of coal slags.